Evaluation of The Relationship Between Communication Skills and Psychosocial Care Skills of Nurses - Hatice Demir; Sevgi Dinç (Atatürk University, 2024)
Objective: The aim of this study is to evaluate the correlation between nurses' communication skills and psychosocial care skills.Methods: The study was a descriptive and cross-sectional quantitative research that was conducted with nurses working in a training and research hospital between January and May 2022. Population of the study consisted of 255 nurses working in the related hospital. The study was completed with a total of 180 nurses who were voluntary to participate in the study and met the inclusion criteria, without using sample selection. A Participant Information Form, the Psychosocial Care Competence Self-Assessment Scale (PCCSAS), and the Communication Skills Inventory (CSI) were used to collect data.Results: It was found that the nurses' communication skills inventory total mean score was 169.65±13.72. There was no significant correlation between the total score of communication skills inventory and the socio-demographic and professional characteristics of the nurses (P>.05). The nurses' PCCSAS total mean score was 64.28±13.13. The PCCSAS total score differed significantly only according to the unit worked and the number of patients per nurse (P=.008; P=.040). There was a statistically significant and positive correlation between CSI total score and PCCSAS total score (r=0.242; P<.01).Conclusion: It is thought that training should be organised at regular intervals for nurses to improve their knowledge and skills about communication and psychosocial care, and the efficiency of the training should be evaluated periodically for patient and nurse groups.